The relationship between trait psychopathy and emotional intelligence: a meta-analytic review. - Megías-Robles, Alberto; Gómez-Leal, Raquel; Gutiérrez-Cobo, María José; Cabello-González, Rosario; Fernández-Berrocal, Pablo (My University, 2018)
Psychopathy is a personality construct that has been related to important emotional deficits. These findings have led to a growing interest in exploring if psychopathic traits are associated with emotional intelligence (EI). However, the literature exploring this association has revealed conflicting results. The aim of the present study was to provide a reliable estimate of the relationship between psychopathy traits and EI (measured as performance-based ability) through meta-analysis. A quantitative and systematic review of the literature using Scopus, Medline, Pubmed, and PsicINFO showed a total of 13 studies meeting inclusion criteria with a combined sample of 2401 participants. The meta-analysis revealed a significant negative relationship between both constructs, showing that higher psychopathic trait scores are related to lower EI levels. We propose several future research lines to clarify possible gaps and ambiguities in the current literature and a set of interesting clinical implications for the prevention, evaluation, and treatment of psychopathic traits by including EI factors in traditional models of psychopathy.
Política de acceso abierto tomada de: https://v2.sherpa.ac.uk/id/publication/15182
Keywords: Sociopatía; Inteligencia emocional; Emotional Intelligence; Psychopathy; Performance-based ability model; Meta-analysis